2021
DOI: 10.1021/acssuschemeng.1c03936
|View full text |Cite
|
Sign up to set email alerts
|

Operando Identification of Hydrangea-like and Amorphous Cobalt Oxyhydroxide Supported by Thin-Layer Copper for Oxygen Evolution Reaction

Abstract: This work demonstrates the unique three-dimensional (3D) layered hydrangea-like structure of amorphous CoOOH, which is deposited on thin-layer copper and nickel foam (CoOOH/Cu/Ni foam), showing the high activity of the oxygen evolution reaction (OER) at an overpotential of 260 mV with a current density of 10 mA cm −2 . The CoOOH/Cu/Ni foam durability test shows almost no decay after 1000 cycles. The cell using the CoOOH/Cu/Ni foam for water electrolysis demonstrates a very stable current density of about 110 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 65 publications
0
12
1
Order By: Relevance
“…This is in perfect agreement with the nominal Co oxidation state in CoOOH and excludes the presence of O vacancies. These findings differ from other studies where an average oxidation state significantly lower than 3 was found on the as-prepared samples. , In the case of Co 3 O 4 , α = 2.54 in air, which departs from the expected 2.66 value. After immersion in the electrolyte, α = 2.62.…”
Section: Resultscontrasting
confidence: 99%
“…This is in perfect agreement with the nominal Co oxidation state in CoOOH and excludes the presence of O vacancies. These findings differ from other studies where an average oxidation state significantly lower than 3 was found on the as-prepared samples. , In the case of Co 3 O 4 , α = 2.54 in air, which departs from the expected 2.66 value. After immersion in the electrolyte, α = 2.62.…”
Section: Resultscontrasting
confidence: 99%
“…An increase in the cell temperature makes the kinetics faster as well as diminishes the thermodynamic potential. , Moreover, an alkaline pH is necessarily chosen due to the minimum water oxidation potential. Although a majority of the transition-metal-based catalysts outperform under alkaline conditions, they behave as electro­(pre)­catalysts and transform into metal-oxy-hydroxides in situ. As a result of the high alkaline stability of transition-metal-oxy-hydroxides such as NiO­(OH), FeO­(OH), and CoO­(OH), they are often studied as efficient OER electrocatalysts. , However, the inferior conductivity of these oxides or oxyhydroxides is the potential bottleneck to achieve the highest activity. Second, metal doping is found to be effective to improve conductivity as well as activity. , For instance, Fe x Ni 1– x O­(OH) is found to be the most reactive transition-metal-based catalyst. Detailed studies have found that the incorporation of Fe into NiO­(OH) or CoO­(OH) leads to a higher OER activity, and this is due to the improved conductivity by the Ni/Co centers, while Fe is considered as the active site .…”
Section: Introductionmentioning
confidence: 99%
“…Together, the XANES features in the post-reaction sample resemble reported profiles of CoOOH, consistent with reports of Co-based electrocatalysts in alkaline solutions. 69,70…”
Section: Resultsmentioning
confidence: 99%